Micro‐mechanical analysis of one‐dimensional compression of clay with DEM - Wang, Pei; Yin, Zhen‐Yu; Hicher, Pierre‐Yves; Cui, Yu‐Jun (International journal for numerical and analytical methods in geomechanics, 2023)
In order to clarify the micro‐mechanics of clay during compression, the behavior of clay subjected to one‐dimensional compression is investigated at the particle scale using discrete element method (DEM). The flaky clay particles in the simulation are approximated by clumps made of spheres. A new contact model is implemented to account for the double‐layer repulsive force, the van der Waals attractive force and the mechanical contact force. The effect of sphere arrangement in the particle clump is discussed. The DEM model is validated against experimental observations in terms of macroscopic compressibility, particle dip angle as well as the over consolidated behavior. The e ‐log σ v curve shows a concave‐to‐linear shape. The evolution of dip angle of clay particles indicates that particles tend to have an anisotropy with a preferential orientation towards horizontal direction. The increase of preconsolidation pressure decreases the initial compressibility due to the increase the number of mechanical contacts. The evolution of average coordination and sphere‐sphere contact shows that the majority of mechanical contacts are generated before the compressive stress reaches 100 kPa. Evolution of soil fabric is presented and discussed.